PEWARISAN DAN PENDIDIKAN IMAN ANAK SEBAGAI TANGGUNG JAWAB ORANGTUA MENURUT ECCLESIA DOMESTICA Studi Kasus Paroki Santo Yosep Purwokerto Timur - Oktavianus Hery Setyawan (P3TK, Sanata Dharma University, 2014)
The Second Vatican Councils document Actuocitatem Apostolicam, said that parents and educators are the first and foremost heralds of the faith to their children's.Based on this background, the author conducted a field study of the Catholic families who are active in the church activities and who provide a good education to their children. The method of research is a qualitative one. As a researcher, the author conducted in-depth interviews with selected five families (parents and children) as informants. After collecting data, the author makes an analysis of the data, an executive summary, a conclusion of the study, an theological reflection, and pastoral recommendations .Finally, the author concludes that the inheritance of faith and education from parents to their children is very effective. Inheritance and parenting education faith which are done properly, produces an improved childs faith. The duties and responsibilities of a parent things in the inheritance of the children's faith and education is very important. Moreover, the challenges of today's believers live very serious. So, the child who has a strong foundation of faith will be able to face the actual or modern challenges.